K-State Turfgrass Research 2011 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2011)
Turfgrass Research 2011 contains results of projects conducted by Kansas State University faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day, August 4, 2011, at the John C. Pair Horticultural Research Center in Olathe, Kan. Articles included in this Report of Progress present summaries of research projects that were completed recently or will be completed in the next year or two. Specifically, this year's report presents summaries of research on turf and the environment, pest control, and turf evaluations.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1053; Kansas Agricultural Experiment Station contribution; no. 11-345-S; Turfgrass; Pest management; Buffalograss; Zoysiagrass; Creeping Bentgrass; Kentucky Bluegrass